Layers of Trauma: the Yiddish-Hebrew Fiction of Yosl Birshteyn (1920-2003) - Waldinger, Albert (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis article evaluates the function of Yiddish-Hebrew creative diglossia in the work of Yosl Birshteyn, a prominent Israeli novelist and short-story writer, particularly in the “first Kibbutz novel” in Yiddish, Hebrew-Yiddish fiction based on the Israeli stock market crash, and the future of Yiddishism in Hebrew and Yiddish. In short, Yiddish acts as a layer of all texts as a fact of communal pain and uncertainty in past, present and future. Birshteyn’s Hebrew originals were translated back into Yiddish and his Yiddish work was translated into Hebrew by famous and representative hands with stylistic and linguistic consequences examined here.